Perilaku Elit Politik Ala Selebriti - Ahmad Al Yakin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2013)
Selebritisasi political phenomenon is rampant in Indonesia formulate study on the behavior of the political elite and the social meaning of waking up celebrity -style political behavior . Therefore, it is necessary to study to be formulated why political elites tend to use celebrity -style political maneuvering , which can contribute both theoretical and practical science . Political elite celebrity -style behavior is a phenomenon of the post-reform political pragmatism , is a product of socialization that comes as one of the factors that influence the behavior of the public and political choice . Society will impose their political choices based on information he received , which also turned out to be a political choice correlated with environmental conditions in which people lived . This makes the political choice of each person is different . Voters turn out to vote based on the information and knowledge gained about the party 's profile , figure candidates , as well as the vision and mission , but also there are voters turn out to vote despite the very minimal knowledge about the parties , candidates and also the vision and mission